Saudi Translation Project (2000-2015): A Historiographical Bibliometric Study - Al-Otaibi, Ajayb A. (2015)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Ajayb A. Al-Otaibi entitled, "Saudi Translation Project (2000-2015): A Historiographical Bibliometric Study," submitted in October 2015. Thesis advisor is Dr. Said Faiq. Soft and hard copy available.